1989
DOI: 10.1084/jem.170.3.847
|View full text |Cite
|
Sign up to set email alerts
|

The monocyte-derived neutrophil activating peptide (NAP/interleukin 8) stimulates human neutrophil arachidonate-5-lipoxygenase, but not the release of cellular arachidonate.

Abstract: LPS and mitogen-stimulated mononuclear cells secrete a cytokine, which is able to activate the PMNL-arachidonate-5-lipoxygenase. This cytokine has been proven to be identical with the recently characterized novel neutrophil-activating peptide NAP/IL-8. NAP/IL-8 is able to activate human PMNL for release of LTB4, omega-oxidized LTB4, and 5-HETE in the presence of exogenous AA. Half-maximal concentration of NAP/IL-8 for release of LTB4 has been found to be near 4 x 10(-8) mol/liter. Time course studies revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(77 citation statements)
references
References 40 publications
6
71
0
Order By: Relevance
“…4,27,35,[37][38][39] In addition to their roles in neutrophil recruitment, TNF␣, IL-1␤, and especially IL-8 promote neutrophil-mediated tissue injury by stimulating neutrophil degranulation and the extracellular release of arachidonic acid metabolites, toxic oxygen radicals, and proteolytic enzymes. 6,10,13,[28][29][30] Our findings indicate that IL-8 is the dominant inflammatory cytokine expressed within the lungs during the acute phase of BPP. Throughout the 24 hour period following inoculation of P. haemolytica, IL-8 was expressed in much greater quantities than either TNF␣ or IL-1␤.…”
Section: Discussionmentioning
confidence: 99%
“…4,27,35,[37][38][39] In addition to their roles in neutrophil recruitment, TNF␣, IL-1␤, and especially IL-8 promote neutrophil-mediated tissue injury by stimulating neutrophil degranulation and the extracellular release of arachidonic acid metabolites, toxic oxygen radicals, and proteolytic enzymes. 6,10,13,[28][29][30] Our findings indicate that IL-8 is the dominant inflammatory cytokine expressed within the lungs during the acute phase of BPP. Throughout the 24 hour period following inoculation of P. haemolytica, IL-8 was expressed in much greater quantities than either TNF␣ or IL-1␤.…”
Section: Discussionmentioning
confidence: 99%
“…Such a direct effect assumes that binding of IL-8, or one of the other ELR ϩ chemokines, to CXCR2 induces the production of proinflammatory mediators, or induces the expression of a molecule that stimulates mediator production. In this regard, IL-8 has been shown to induce the production of LTB 4 and LTC 4 by neutrophils and IL-3-treated basophils, respectively (56,57). In addition, IL-8 has been reported to enhance the expression of cyclooxygenase-2, which catalyzes the formation of PGs such as PGE 2 , by LPS-stimulated neutrophils (58), and to act in an autocrine fashion, inducing monocyte IL-8 production (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some studies showed that H pylori infection released mediators and chemokines including interleukin (IL)-8, inducible nitric oxide synthase, and COX-2 in considerable levels; among these mediators, IL-8 could stimulate lipid metabolites through modulating LOX activities [15][16][17][18][19]. Furthermore, H pylori-provoked cytokine-mediated inflammatory responses can be neutralized by blocking 5-LOX that metabolized arachidonic acid (AA) into 5(S)-HETE, a precursor metabolite of leukotrienes B 4 (LTB 4 ), suggesting that LOX pathway as much as COX induction could be principally engaged in pathogenic mechanism of H pylori infection.…”
Section: Abstract Helicobacter Pylori Red Ginseng 5(s)-hete 5-lmentioning
confidence: 99%